PERAN HUBUNGAN INDUSTRIAL YANG HARMONIS EFEKTIF DALAM MEMPERKUAT PENYELESAIAN SENGKETA ANTARA PEKERJA DAN PENGUSAHA - Syivana Nabila; Anissa Putri Amelia; Anang Dony Irawan (Universitas Nurul Jadid, 2026)
The harmonious industrial relationship is an important foundation in creating labor stability and increases the effectiveness of dispute resolve between workers and entrepreneurs. The problem of issue in this study is: (1) What are the elements that make up the creation of harmonious industrial relations between workers and entrepreneurs? And (2) How the role of harmonious industrial relations in strengthening and improving the effectiveness of dispute resolve between workers and entrepreneurs, both in the prevention and resolution of conflict. This study uses normative juridical methods by reviewing the provisions of positive law, especially Law Number 13 Year 2003 on Employment and Law Number 2 Year 2004 concerning Settlement of Industrial Relationship Dispute. The results showed that the harmonious industrial relations was built through the fulfillment of workers' normative, public open communication, the actual role of unions, as well as government surveillance. The harmony is functioning not only as a dispute for dispute, but also accelerates the resolution of conflict through bipartite, mediation, conciliation, and arbitration mechanisms. Stable industrial relations proved to create a healthy social dialogue climate, minimizing the escalation of conflict to industrial relations, and improving time efficiency, cost, and energy in dispute resolution. Thus, strengthening the industrial relations becomes a key factor in realizing effective, equitable and sustainable dispute resolution for workers or entrepreneurs.